A convergent parallel mixed-methods study of peer-mediated creative partnership on critical thinking and reading comprehension among indonesian EFL senior high school students - Farih Nur Firdaus; Daniar Sofeny; Buyun Khulel; Khoirul Huda; Syifa Khuriyatuz Zahro; Irmayani Irmayani; Anita Dwi Hapsari (Journal of Counseling, Education and Society, 2026)
This convergent parallel mixed-methods study examined the effect of a six-week, peer-mediated Creative Partnership intervention on the critical thinking and reading comprehension of 32 senior high school EFL students (aged 15–17, intermediate/CEFR B1 proficiency) at a senior high school in East Java, Indonesia, and explored how the intervention reshaped classroom interaction. Quantitative data were collected using a researcher-developed, expert-validated pre-/post-test measuring literal, inferential, and evaluative comprehension aligned with Bloom’s Revised Taxonomy (Cronbach’s α = .87) and analyzed with a paired-sample t-test and Cohen’s d. Qualitative data classroom observation (Cohen’s κ = .82), semi-structured interviews, and reflective journals were analyzed through the thematic coding procedure of Miles, Huberman, and Saldaña. Results indicated a statistically significant overall gain in reading comprehension, t(31) = 10.21, p < .001, 95% CI [13.44, 20.14], with a very large effect size (d = 1.81); evaluative comprehension improved the most (36.4%, d = 2.35), followed by inferential (29.4%, d = 2.15) and literal comprehension (19.3%, d = 1.84). Thematic analysis identified four convergent patterns: dialogic co-construction of meaning, emergence of critical and reflective thinking, collaborative creativity and engagement, and the teacher’s repositioning as co-learner. The integration of both strands suggests that structured creative partnership functions as a cognitive, social, and affective scaffold that moves students from literal decoding toward higher-order interpretation. Findings support Creative Partnership as a promising pedagogical model for developing critical thinking and reading comprehension in EFL classrooms, while the single-group, single-site design underscores the need for controlled, multi-site replication before broad claims of effectiveness are warranted.